2013
DOI: 10.1186/1471-2482-13-s2-s37
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of BRAF V600E mutation testing in thyroid nodules in elderly patients

Abstract: BackgroundThyroid cancer is a rare disease characterized by the subtle appearance of a nodule. Fine-needle cytology (FNC) is the first diagnostic procedure used to distinguish a benign from a malignant nodule. However, FNC yields inconclusive results in about 20% of cases. BRAFV600E mutation is the most frequent genetic alteration in papillary thyroid carcinoma (PTC); its high prevalence makes this oncogene a useful marker to refine inconclusive FNC results. However, the prevalence of the BRAFV600E mutation de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Several studies have demonstrated the superiority of the VATS approach over sternotomy such as a smaller incisions with better cosmesis and less trauma to the chest wall, a decreased post-operative stay, a complete remission and no difference in outcome as compared to the open approach allowing an early adjuvant chemo-radiation treatment in advanced cases. However, most of the authors use the VATS approach when the tumor diameter is less than 5 cm or 6 cm, not involving the innominate vein, with little or no evidence of invasion or compression of major mediastinal structures [32] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] . Furthermore, VATS is considered a better approach for less intra-operative blood loss and early removal of chest drains.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the superiority of the VATS approach over sternotomy such as a smaller incisions with better cosmesis and less trauma to the chest wall, a decreased post-operative stay, a complete remission and no difference in outcome as compared to the open approach allowing an early adjuvant chemo-radiation treatment in advanced cases. However, most of the authors use the VATS approach when the tumor diameter is less than 5 cm or 6 cm, not involving the innominate vein, with little or no evidence of invasion or compression of major mediastinal structures [32] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] . Furthermore, VATS is considered a better approach for less intra-operative blood loss and early removal of chest drains.…”
Section: Discussionmentioning
confidence: 99%
“…It is less frequent amongst young people and increases progressively with age [10]. Frequent use of sensitive diagnostic techniques such as high-resolution ultrasonography, computerised tomography, and magnetic resonance or positron emission tomography may be responsible for incidental detection of thyroid tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of the BRAF V600E mutation has high specificity and a positive prediction value (PPV) for PTC [7]. Nevertheless, it is important to consider that the prevalence of the BRAF V600E mutation depends on its detection methods, geographical factors, and age [10]. The object was to determine the value of reassessing the presence of the BRAF V600E mutation in making the diagnosis of PTC.…”
Section: Introductionmentioning
confidence: 99%
“…These AVMs increase in size during pregnancy [3]. The differential diagnosis was for: abnormal systemic vessels, highly vascular parenchymal mass, other congenital or acquired pulmonary arterial or venous lesions (e.g pulmonary varix), retroperitoneal varices [11,16,2132]. …”
Section: Discussionmentioning
confidence: 99%